Analysis of River Bed Cracking Above Longwall Extraction Panels in the Southern Coalfield of New South Wales, Australia - Sainsbury, DP (SHIRMS 2008: Proceedings of the First Southern Hemisphere International Rock Mechanics Symposium, 2008)
Mining-induced subsidence has adversely impacted the near surface hydrologic cycle and natural surface topography above longwall extraction panels in the Southern Coalfield of New South Wales (NSW), Australia. The distinct element method programme PFC enables simulation of the mechanical behaviour of rock, which is governed by the formation, growth and eventual interaction of microcracks to form explicit fractures. The PFC analysis accurately simulates the monitored surface subsidence, together with the evolution, location and orientation of the explicit fractures that were observed after longwall development. Analysis of the explicit fracturing provides a greater understanding of the altered near-surface hydrologic cycle and enables effective rehabilitation of the damaged river beds.